Enhancing primary students’ understanding of social studies through the Jigsaw approach - Rosmawijah Jawawi; Zarinah Mahari; Yusimah Amjah; Shamsinar Husain; Nur-Ashikin Petra; Lilly Suzana Shamsu (Intelektual Pustaka Media Utama, 2019)
This study aimed to examine the implementation of the Jigsaw approach in teaching primary social studies in Brunei Darussalam. The topic selected for this study was on 'The Reign of Sultan Omar Ali Saifuddien III 1950 – 1967’. The sample consisted of 25 primary students in a Year 6 class. The methodology of this study was an action research. Among the instruments used were tests, observations, interviews, and students' journals. The findings showed that the students' test results had improved, indicating the effectiveness of the Jigsaw approach in teaching social studies. It was observed that there were positive developments in students’ communication skills as well as their participation in the class activities. The students' motivation to learn was mostly positive as they enjoyed learning cooperatively in the given activities. However, the challenge of implementing this Jigsaw approach was the role of the teacher as a facilitator in this approach. Future research should continue to examine the different ways of teaching social studies that could involve students' active participation in the teaching and learning process.